A novel function of API5 (apoptosis inhibitor 5), TLR4-dependent activation of antigen presenting cells. (3rd October 2018) - Kim, Young Seob; Park, Hyun Jin; Park, Jung Hwa; Hong, Eun Ji; Jang, Gun-Young; Jung, In Duk; Han, Hee Dong; Lee, Seung-Hyun; Vo, Manh-Cuong; Lee, Je-Jung; Yang, Andrew; Farmer, Emily; et al.
ABSTRACT: Dendritic cell (DC)-based vaccines are recognized as a promising immunotherapeutic strategy against cancer. Various adjuvants are often incorporated to enhance the modest immunogenicity of DC vaccines. More specifically, many of the commonly used adjuvants are derived from bacteria. In the current study, we evaluate the use of apoptosis inhibitor 5 (API5), a damage-associated molecular pattern expressed by many human cancer cells, as a novel DC vaccine adjuvant. We showed that API5 can prompt activation and maturation of DCs and activate NFkB by stimulating the Toll-like receptor signaling pathway. We also demonstrated that vaccination with API5-treated DCs pulsed with OVA, E7, or AH1-A5 peptides led to the generation of OVA, E7, or AH1-A5-specific CD8 + T cells and memory T cells, which is associated with long term tumor protection and antitumor effects in mice, against EG.7, TC-1, and CT26 tumors. Additionally, we determined that API5-mediated DC activation and immune stimulation are dependent on TLR4. Lastly, we showed that the API5 protein sequence fragment that is proximal to its leucine zipper motif is responsible for the adjuvant effects exerted by API5. Our data provide evidence that support the use of API5 as a promising adjuvant for DC-based therapies, which can be applied in combination with other cancer therapies. Most notably, our results further support the continued investigation of human-based adjuvants.